Hybrid Leadership Models In Education And Their Contribution To Organizational Learning And Institutional Resilience - Nur Efendi (Pondok pesantren As-salafiyah As-Safi'iyyah, 2025)
This study investigates hybrid leadership models and their contribution to organizational learning and institutional resilience at SMK PGRI 01 Tulungagung. The research addresses how hybrid leadership is practiced, how it supports organizational learning, and how it strengthens institutional resilience within a vocational education context. A qualitative case study design was employed to explore leadership practices in a natural institutional setting. Data were collected through semi-structured interviews, observations, and document analysis involving the principal, teachers, and administrative staff. The findings reveal that hybrid leadership integrates transformational, instructional, and distributed approaches, creating flexible leadership practices that align vision, collaboration, and instructional improvement. Organizational learning is developed through reflective practice, professional dialogue, and collaborative problem-solving embedded in daily activities. Institutional resilience is demonstrated through the school’s capacity to adapt to challenges, maintain performance, and sustain coordinated responses to change. The study identifies a dynamic interaction where leadership practices facilitate learning, learning enhances adaptability, and adaptability strengthens resilience. These findings indicate that hybrid leadership plays a significant role in fostering sustainable development and responsiveness in vocational educational institutions.